2020
DOI: 10.3390/ijms21072302
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Break Properties of Protoporphyrin IX by X-ray Irradiation against Melanoma

Abstract: Recent reports have suggested that 5-aminolevulinic acid (5-ALA), which is a precursor to protoporphyrin IX (PpIX), leads to selective accumulation of PpIX in tumor cells and acts as a radiation sensitizer in vitro and in vivo in mouse models of melanoma, glioma, and colon cancer. In this study, we investigated the effect of PpIX under X-ray irradiation through ROS generation and DNA damage. ROS generation by the interaction between PpIX and X-ray was evaluated by two kinds of probes, 3′-(p-aminophenyl) fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…We previously reported that the photosensitizer Verteporfin, which is already used for liposomal formulation in clinical practice, can function as an RDT agent, which is important for accelerating the eventual clinical translation of this modality [16][17][18][19]. Similar findings for other PSs (e.g., protoporpyrin IX) have been reported by other groups [20][21][22]. As we have recently reviewed in detail [23], the mechanisms of ROS generation in RDT are not fully understood but include direct PS activation by secondary electrons, the use of scintillation nanocrystals to convert X-ray energy into light, and PS activation by the Cerenkov light generated by high-energy secondary electrons produced in tissue by MeV X-rays.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…We previously reported that the photosensitizer Verteporfin, which is already used for liposomal formulation in clinical practice, can function as an RDT agent, which is important for accelerating the eventual clinical translation of this modality [16][17][18][19]. Similar findings for other PSs (e.g., protoporpyrin IX) have been reported by other groups [20][21][22]. As we have recently reviewed in detail [23], the mechanisms of ROS generation in RDT are not fully understood but include direct PS activation by secondary electrons, the use of scintillation nanocrystals to convert X-ray energy into light, and PS activation by the Cerenkov light generated by high-energy secondary electrons produced in tissue by MeV X-rays.…”
Section: Introductionsupporting
confidence: 75%
“…In general, RDT in its various forms with different photosensitizers has shown both in vitro and in vivo efficacy across in a range of tumor types [16][17][18][20][21][22][55][56][57][58]. Nevertheless, it is not clear that the efficacy is enough to translate into a stand-alone treatment using a well-tolerated (e.g., <10 Gy) dose of high-energy (MeV) X-rays combined with systemic administration of an approved clinical photosensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the accumulation of reactive oxygen species (ROS) results in the appearance of oxidative stress. Numerous studies indicate that DNA repair mechanisms (mainly BERs) are activated in response to oxidative DNA damage (oxidized DNA bases, DNA single-and double-strand breaks) [41][42][43][44][45]. In human cells it was demonstrated that the presence of hydrogen peroxide and tertiary-butyl hydro peroxide causes ROS accumulation leading to oxidative stress which results in induction of DNA damage also in the form of DNA breaks [46].…”
Section: -Bromopyruvate (3-bpmentioning
confidence: 99%
“…induce DNA damage, combined radiation therapy treatment with 5-ALA is expected to improve therapeutic efficacy for radioresistant melanoma [26].…”
Section: Inhibition Of Melanogenesis Can Improve Radiotherapy Modalit...mentioning
confidence: 99%